2008
DOI: 10.5194/angeo-26-1837-2008
|View full text |Cite
|
Sign up to set email alerts
|

Imaging radar observations of Farley Buneman waves during the JOULE II experiment

Abstract: Abstract. Vector electric fields and associated E×B drifts measured by a sounding rocket in the auroral zone during the NASA JOULE II experiment in January 2007, are compared with coherent scatter spectra measured by a 30 MHz radar imager in a common volume. Radar imaging permits precise collocation of the spectra with the background electric field. The Doppler shifts and spectral widths appear to be governed by the cosine and sine of the convection flow angle, respectively, and also proportional to the presum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 34 publications
4
27
0
Order By: Relevance
“…The rocket measurements were mapped along geomagnetic field lines to the E region scattering volume and compared with the Doppler spectra of echoes arising from that volume. Confirming the results of Bahcivan et al (2005) and Hysell et al (2008) found empirical relationships between the moments of the spectra (Doppler shifts, spectral widths) and the corresponding line-of-sight and crosstrack components of the electron drift velocity. Using these empirical formulas, they were able to predict the spectral moments on the basis of the electric fields measured in situ.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…The rocket measurements were mapped along geomagnetic field lines to the E region scattering volume and compared with the Doppler spectra of echoes arising from that volume. Confirming the results of Bahcivan et al (2005) and Hysell et al (2008) found empirical relationships between the moments of the spectra (Doppler shifts, spectral widths) and the corresponding line-of-sight and crosstrack components of the electron drift velocity. Using these empirical formulas, they were able to predict the spectral moments on the basis of the electric fields measured in situ.…”
Section: Introductionsupporting
confidence: 69%
“…The empirical formulas used by Hysell et al (2008) relating the spectral moments (Doppler shift and spectral width) to the The first three beams point west of the magnetic meridian, and the next three point east. Beam pairs 0 and 3, 1 and 4, and 2 and 5 are symmetric about the magnetic meridian.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…The small rotation of the propagation direction of the waves with respect to the flow angle was also recovered and is a consequence of thermal effects . The same dependencies were also found by comparing VHF imaging radar and sounding rocket observations of Farley-Buneman waves in the auroral zone by Hysell et al [2008], who expanded on the formalism of St-Maurice [1993a, 1993b] in proposing a theoretical/ phenomenological model for the behavior. Similar behavior has not been observed by fixed-beam HF and VHF radars operating at auroral latitudes [Makarevich, 2009], although inferring it without the benefits of radar imaging or the simple geometry available at Jicamarca would be difficult.…”
Section: Farley-buneman Gradient Drift Instabilitysupporting
confidence: 51%
“…Direct measurements in the waves using instrumented sounding rockets, as analyzed recently by Hysell et al [2008] and Krane et al [2010], offer rare but particularly incisive views into the microphysics of the instabilities at work. (See the works of Pfaff [1995], however, for a discussion of the experimental complications involved.)…”
Section: Introductionmentioning
confidence: 99%